The Relationship between Motivational Factors and Classroom Engagement Behaviors among Secondary School Students: A Multidimensional Analysis - Dr. Ambreen Siddique; Asma; Sobia Younas (Indus Journal of Social Sciences, 2025)
The purpose of this study was to investigate the effect of motivation on students’ classroom engagement at the secondary school level. It was quantitative research that employed a survey research correlational research design. The population of the study was all the secondary school students in one district of Punjab province. The convenient sampling technique was used to select 211 students as participants of the study. The data were collected through a self-developed five-point Likert scale questionnaire with twenty-five items. The data were analyzed through SPSS (Statistical Package for Social Sciences) version 22. Descriptive statistics (Mean & Standard deviation) and inferential statistics (t-test and correlational) were employed to check the mean difference between different variables. The findings of the study show that there was a strong and positive relationship between the students’ motivation and classroom engagement. Whereas by gender, sector and age, female, 9th-grade students, and private students' mean scores were different and better than male public school students and 10th grade students. Based on the result, it was recommended that the differences in motivation and engagement between private and public school students suggest a need for improved teaching methods, resources, and student support in public schools.